The Impact of Rubric Implementation on Enhancing Speaking Skills in Generation Z Students within the Merdeka Curriculum Framework - Astrini, Atik; Mauly Halwat Hikmat; Muamaroh (PT. Banjarese Pacific Indonesia, 2024)
This study explores the role of rubrics in improving speaking skills among Generation Z students under the Merdeka Curriculum in Indonesia. By leveraging qualitative research methods, specifically in-depth interviews with experienced English language teachers, the study delves into the practical applications, benefits, and challenges of rubric implementation. The findings reveal that rubrics significantly enhance student performance by providing clear, structured, and detailed feedback, aligning with Generation Z's preference for interactive and visually engaging learning experiences. Additionally, the study highlights the compatibility of rubrics with the objectives of the Merdeka Curriculum, emphasizing student independence and creativity. These insights underscore the necessity for educators to adopt and refine rubric-based assessments to meet contemporary educational goals and the unique characteristics of modern learners.